Cinobufacini protects against paclitaxel-induced peripheral neuropathic pain and suppresses TRPV1 up-regulation and spinal astrocyte activation in rats - Xiyuan Ba; Jiali Wang; Shiyang Zhou; Xinxin Luo; Yun Peng; Shimin Yang; Yue Hao; Guangyi Jin (2018)
Chemotherapy-induced peripheral neuropathic pain is a major limiting factor affecting cancer patients. No effective treatment is currently available. Cinobufacini, an aqueous extract from toad skin, is a widely used anti-cancer drug in China. Clinical evidence has demonstrated the safety and effectiveness of cinobufacini in combination with chemotherapy to promote the therapeutic efficacy while alleviating side effects, especially cancer-related pain symptoms. In this study, the effects of cinobufacini were investigated in a rat model of paclitaxel-induced peripheral neuropathic pain (PIPNP) to better understand and expand its clinical application. A single injection of cinobufacini (2.5 g/kg, i.p.) alleviated pre-established PIPNP, as indicated by decreased mechanical and thermal hypersensitivity compared with paclitaxel-treated rats. Repeated cinobufacini (1.25 and 2.5 g/kg, i.p.), given during the induction of PIPNP, prevented the establishment of paclitaxel-induced mechanical and thermal hypersensitivity. This preventative effect was associated with suppressed paclitaxel-induced TRPV1 up-regulation and spinal astrocyte activation, as well as decreased production of spinal TNF-α and IL-1β. These findings reveal cinobufacini as a therapeutic potential to treat and prevent paclitaxel-induced peripheral neuropathic pain.